PROJETO MAIS MÉDICOS PARA O BRASIL: Percepção da tutoria e supervisão acadêmica sobre a qualificação dos médicos no Maranhão - NERIS FILHO, Jonas (2024)
Introduction: The Mais Médicos para o Brasil Project (PMMB), created within the context of the Mais Médicos Program, represents an initial pillar for achieving universal health rights guaranteed by the 1988 Constitution, with an emphasis on expanding and strengthening Primary Health Care. The Project contributes to medical training by enabling the improvement of professionals in Primary Health Care units of the Unified Health System, through lato sensu and/or stricto sensu improvement and specialization courses, offered by teaching and research institutions, incorporating a healthcare component, based on the integration between teaching and service. Objective: To understand the processes and impacts of the Mais Médicos Project in Maranhão on the qualification of doctors for primary health care from the perspective of academic tutoring and supervision. Methodology: This is an exploratory study with a qualitative approach. Data were collected between August and October 2024, through semi-structured interviews, applied to academic tutors and supervisors who work at PMMB in the state of Maranhão, linked to the Federal University of Maranhão. The research was authorized by the General Coordination of Expansion and Management of Health Education of the Ministry of Education and approved by the Research Ethics Committee of the Presidente Dutra University Hospital of the Federal University of Maranhão (HU/UFMA), under Opinion No. 6,793,664. Results: 24 participants participated in the research, being 04 academic tutors and 20 supervisors, predominantly individuals aged 30 to 39 years (45.84%), the majority being women (54.16%). Bardin's content analysis technique was used, and three thematic categories emerged: Perception of academic tutors and supervisors about the PMMB, pedagogical proposals and educational strategies in the academic supervision of the PMMB, and qualification of doctors for primary care from the perspective of the Academic Supervision of the PMMB. Final Considerations: The research allowed us to understand the processes and impacts of the Mais Médicos Project in Maranhão in the qualification of doctors for Primary Health Care (PHC) from the perspective of tutoring and academic supervision, understanding the important role of the University in the training of participating doctors for the development of skills that contribute to a more comprehensive and problem-solving PHC.